TO POLITICISE OR NOT TO POLITICISE? THE CASE OF MANAGERS IN LITHUANIAN PERSONAL HEALTH CARE ORGANISATIONS - Likaitė, Dovilė (Politologija, 2014)
Previous studies have shown that politicisation can penetrate into the areas that are not directly related to politics. This article deals with the change and politicisation of managers in Lithuanian personal health care organisations in the period 1997–2013. A lack of understanding of the underlying mechanism for politicisation of the healthcare system is a problem, as the number of politicised managers in personal health care organisations exceeds 50%. The analysis revealed that political parties do not make decisions on politicisation in a centralised way. Party organisations are miniature political systems which encompass regional political leaders with different motives and divergent views. In spite of this fact, the politicisation of managers in personal health care organisations has several common characteristics. Primary health care centres turned out to be the most politicised when compared to hospitals that belong to secondary and tertiary health care levels. Therefore, it may be suggested that the Lithuanian healthcare system is dominated not by power patronage but by service patronage when appointments at the bottom of the healthcare levels are distributed as a mode of vote or support gathering and party network expansion. By all means, it is difficult to capture the direction of politicisation using quantitative methods: do parties appoint loyal people to certain positions or do managers themselves choose to join political party in order to get a job? It can also be associated with the desire to get more privileges to one’s own personal health care organisation. Therefore, inner motivation is the main driver of politicisation. The survival analysis of managers in personal health care organisations showed that motivation stemming from the supply side (e.g. control of the managers) is not the prime explanatory factor of politicisation. These results confirm that politicians do not appoint loyal managers in order to ensure control over the policies implemented inside the organisation. The managers in personal health care organisations could be eager to politicise themselves in a bottom-up way, as belonging to a party ensures greater job stability. These findings allowed rejecting the hypothesis stating that party membership increases the probability of healthcare managers’ turnover. However, these results are consistent with other data provided in the article. Since the change of mayors has no statistically significant impact on politicisation, it could be argued that a managerial position for medical doctors represents a career-high achievement. Therefore, many directors are simply trying to keep their managerial position, unless they are keen on trying their chances in the political arena.